(untitled) (History Journal «Jerónimo Zurita», 2023)
When Bernard of Clairvaux took over the Cistercian Order after the death of his predecessor Stephen Harding in 1134, he was faced with a recently completed rigorist reform of monasticism in the Benedictine tradition. Under his rule, he initiated a second reform, reflected in the oldest liturgical-musical documents of the Order. These documents, most of them palimpsests, have required a long work of interpretation and restitution, which today makes it possible to reveal a forgotten liturgical and musical tradition, the one prior to Bernard and, therefore, that of the first chant that was practiced in the Cistercian order between 1110 and 1143.